O level history and culture of pakistan (topical solved resource pack with marking scheme) 2059 CIE papers 2013-2018 - Khan, Sarah (Excel book company; Karachi, 2006)
O Level History and Culture of Pakistan (Topical Solved Resource Pack with Marking Scheme) 2059 CIE Papers 2013-2018 provides a comprehensive collection of past exam papers with detailed solutions and marking schemes to aid students in their exam preparation.